Neuroborreliosis with encephalitis: a broad spectrum of clinical manifestations - Dominica Hudasch; Franz Felix Konen; Nora Möhn; Lea Grote-Levi; Ulrich Wurster; Gabriel Welte; Josef Conzen; Nima Mahmoudi; Thomas Skripuletz; Philipp Schwenkenbecher (BMC Infectious Diseases)
Abstract Background Lyme neuroborreliosis is the disseminated stage of an infectious disease caused by Borrelia burgdorferi (BB). The most prevalent clinical manifestations include meningoradiculitis and involvement of the cranial nerves with lymphocytic meningitis. Facial nerve is the most frequently affected cranial nerve. Neuroborreliosis presenting as encephalitis is only scarcely described in the literature. Methods Medical records of patients between 2014 and 2024 were screened and reviewed for neuroborreliosis. Patients were only included if they met the diagnostic criteria for definite neuroborreliosis. Results A total of seven patients with neuroborreliosis induced encephalitis were identified. The median age was 72 years, and except for one man, all patients were women. Clinical manifestations ranged from cognitive impairments resembling primary dementia to movement disorders mimicking Parkinson's disease, tremor, and epileptic seizures. In 5/7 patients (71%) they occurred between August to September. In addition to central nervous system involvement, all patients exhibited characteristic features of neuroborreliosis like painful meningoradiculitis or peripheral facial palsy. An elevated cell count in cerebrospinal fluid (CSF), positive oligoclonal bands, and blood-CSF barrier dysfunction indicated by an elevated albumin quotient (QAlb) was found in all patients. Advanced age, in which immunosenescence can occur, might contribute in developing encephalitis caused by neuroborreliosis in the patients of this cohort. Conclusion Neuroborreliosis can present with symptoms that mimic various neurological disorders, such as dementia, movement disorders, and epilepsy. Radiculitis, peripheral facial palsy or meningitis are an additional hint for this infectious disease. Analysis of CSF, which includes testing for intrathecally produced BB antibodies, is crucial for the diagnosis.